2019
DOI: 10.21653/tfrd.416013
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish Version of the Carer’s Assessment of Satisfaction Index (Casi-Tr): Its Validation and Reliability

Abstract: Purpose: Caregivers of patients with chronic diseases could experience positive as well as negative feelings as a result of caregiving. Although there are assessment tools in the literature that are used to measure the satisfaction received from caregiving, which is one of the positive feelings experienced by caregivers, there was no tool that assessed caregiver satisfaction in Turkey. This study aimed to evaluate the reliability and validity of the Turkish version of the Carer's Assessment of Satisfaction Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The Turkish validity and reliability study of the scale was carried out by Duru As¸iret et al and the Cronbach's alpha value was found to be 0.94. 27 The Cronbach's alpha coefficient in this study was 0.92.…”
Section: Instrumentsmentioning
confidence: 52%
“…The Turkish validity and reliability study of the scale was carried out by Duru As¸iret et al and the Cronbach's alpha value was found to be 0.94. 27 The Cronbach's alpha coefficient in this study was 0.92.…”
Section: Instrumentsmentioning
confidence: 52%